Transportation security against terrorism - Tahmisoğlu, Mete; Özen, Cinar (NATO science for peace and security series. Human and societal dynamics, 2009)
Even a cursory review of the numerous hijacking, train and bus bombings can establish beyond doubt that transport systems are particularly vulnerable targets of terrorist attack. This book intends to offer the groundwork for a theoretical and practical understanding of the issues that surround transportation security against terrorism.